Harnessing the power of spaced repetition learning and active recall for trainee education in otolaryngology - Marinelli, John P.; Hwa, Tiffany P.; Lohse, Christine M.; Carlson, Matthew L. (American journal of otolaryngology, 2022)
Medical education is rapidly evolving. The historical reliance on textbook reading is being increasingly replaced by trainees in favor of using non-traditional platforms such as podcasts, videos, and app-based learning. Neuroscience research on human learning has demonstrated superior long-term retention when the synergistic principles of spaced repetition and active recall are employed. Spaced repetition entails the repeated exposure to learned material over successive iterations, whereas active recall involves the intentional reconstructive process of retrieving previously learned material, often through prompting (e.g., answering open-ended questions without multiple choice answers), rather than passively reviewing previously learned information (e.g., re-reading a textbook chapter). These concepts have revolutionized medical student education, with use of open-source spaced repetition platforms, such as Anki, and question banks becoming ubiquitous. Paralleling educational platforms within otolaryngology are emerging. Headmirror's OtoRecall app provides a free, peer-reviewed, open-access option for otolaryngology trainees to harness the power of these learning principles.